DENYING THE EXISTENSE OF THE UKRAINIAN NATIONAL STATE IN THE HISTORICAL RESEARCH OF THE UKRAINE SSR: END OF THE 60’S – 70’S OF THE XXTH CENTURY - Kindrachuk, Nadiya Myroslavivna (Torun International Studies, 2018)
The question of the Ukrainian national idea and processes of the Ukrainian state-building in the historical science of the Ukrainian SSR in the late 60’s – during the 70’s of the twentieth century was distorted by the Soviet ideological system. For the communist rule, Ukrainian nationalism was the subject of active speculation and correction of its content in the right direction for the ruling elit. This article examines the end of the 60’s – 70’s of the XX century, the time characterized by intensification of repressive management of historical science in the USSR, the establishment of censorship and harassment, forcing the Ukrainian historians to serve the needs of the Soviet totalitarian state. Rejection of historical science from ideological foundations of the Communist Party was impossible. Ideological supervision of the intelligentsia in Ukraine and total control of historical research institutions started. Ruling Communist Party fought against dissidents, media and folowers of «Ukrainian bourgeois nationalism ideology», shaped prejudice to all national. The least manifestation of patriotism of Ukrainians was regarded as anti-Soviet activity. Ukrainians were reluctantly forced to feel inferior nation without its own long history. The author of this article aims at reproducing an exact picture of the Soviet power’s struggle with the ideology of “Ukrainian bourgeois nationalism” in the historical science of the USSR at the end of the 60’s – during the 1970’s of the XXth century, as well as correction of the historical memory of the Ukrainian people in favour of the formation of a new political community – the “Soviet people”, the establishment and support by administrative means of rigid ideological demands of the conceptual vision, division into periods and the interpretation of the Ukrainian past. After analyzes of the scientific literature, the subject under study remains insufficiently studied. This gives the opportunity to continue working in this promising direction.